BNIP3L/Nix-induced mitochondrial fission, mitophagy, and impaired myocyte glucose uptake are abrogated by PRKA/PKA phosphorylation. Issue 9 (2nd September 2021) - da Silva Rosa, Simone C.; Martens, Matthew D.; Field, Jared T.; Nguyen, Lucas; Kereliuk, Stephanie M.; Hai, Yan; Chapman, Donald; Diehl-Jones, William; Aliani, Michel; West, Adrian R.; Thliveris, James; Ghavami, Saeid; et al.
ABSTRACT: Lipotoxicity is a form of cellular stress caused by the accumulation of lipids resulting in mitochondrial dysfunction and insulin resistance in muscle. Previously, we demonstrated that the mitophagy receptor BNIP3L/Nix is responsive to lipotoxicity and accumulates in response to a high-fat (HF) feeding. To provide a better understanding of this observation, we undertook gene expression array and shot-gun metabolomics studies in soleus muscle from rodents on an HF diet. Interestingly, we observed a modest reduction in several autophagy-related genes. Moreover, we observed alterations in the fatty acyl composition of cardiolipins and phosphatidic acids. Given the reported roles of these phospholipids and BNIP3L in mitochondrial dynamics, we investigated aberrant mitochondrial turnover as a mechanism of impaired myocyte insulin signaling. In a series of gain-of-function and loss-of-function experiments in rodent and human myotubes, we demonstrate that BNIP3L accumulation triggers mitochondrial depolarization, calcium-dependent activation of DNM1L/DRP1, and mitophagy. In addition, BNIP3L can inhibit insulin signaling through activation of MTOR-RPS6KB/p70S6 kinase inhibition of IRS1, which is contingent on phosphatidic acids and RHEB. Finally, we demonstrate that BNIP3L-induced mitophagy and impaired glucose uptake can be reversed by direct phosphorylation of BNIP3L by PRKA/PKA, leading to the translocation of BNIP3L from the mitochondria and sarcoplasmic reticulum to the cytosol. These findings provide insight into the role of BNIP3L, mitochondrial turnover, and impaired myocyte insulin signaling during an overfed state when overall autophagy-related gene expression is reduced. Furthermore, our data suggest a mechanism by which exercise or pharmacological activation of PRKA may overcome myocyte insulin resistance. Abbreviations: BCL2: B cell leukemia/lymphoma 2; BNIP3L/Nix: BCL2/adenovirus E1B interacting protein 3-like; DNM1L/DRP1: dynamin 1-like; FUNDC1: FUN14 domain containing 1; IRS1: insulin receptor substrate 1; MAP1LC3A/LC3: microtubule-associated protein 1 light chain 3 alpha; MFN1: mitofusin 1; MFN2: mitofusin 2; MTOR: mechanistic target of rapamycin kinase; OPA1: OPA1 mitochondrial dynamin like GTPase; PDE4i: phosphodiesterase 4 inhibitor; PLD1: phospholipase D1; PLD6: phospholipase D family member 6; PRKA/PKA: protein kinase, AMP-activated; PRKCD/PKCδ: protein kinase C, delta; PRKCQ/PKCθ: protein kinase C, theta; RHEB: Ras homolog enriched in brain; RPS6KB/p70S6K: ribosomal protein S6 kinase; SQSTM1/p62: sequestosome 1; YWHAB/14-3-3β: tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein beta